(untitled) (Materiali di Estetica. Terza serie, 2022)
The article is devoted to the memory of the late Antonio Rostagno (1962-2021). It focuses on Rostagno’s commitment to musical aesthetics and attempts to highlight his original way of addressing the space between music and philosophy, following Rostagno’s interest in Adorno and Schumann from a historical and theoretical perspective